Revealing EFL Students’ Perception towards the Implementation of Kahoot! in Learning Narrative Text at the Secondary School Level - Melina Cahyaningtyas; Nur Chakim (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2023)
Information and communication technology development has been massive in the last decades. This development allows teachers to utilize internet based applications such as Kahoot! as a learning tool. This present study was conducted to reveal the perception of secondary level students about the use of Kahoot! in learning narrative text. The participants of this study are 66 students of a junior high school in Sidoarjo. The study uses the quantitative method to collect and analyze the data. This study shows that students see Kahoot! in a positive way. They find Kahoot! as a learning tool that may help them improve their activities in class with an engaging environment, resulting in higher academic achievement.